2023
DOI: 10.31616/asj.2021.0481
|View full text |Cite
|
Sign up to set email alerts
|

In Vertebral Hemangiomas with Neurological Deficit, Is a Less Extensive Approach Adequate

Abstract: To analyze the surgical and neurological outcomes following surgical decompression in patients with aggressive vertebral hemangioma (AVH) presenting with neurological deficit and to determine whether a less extensive approach is appropriate. Overview of Literature: AVHs are a rare subset of benign vascular tumors frequently presenting with neurological deficit because of spinal cord compression. Though the results of surgical management have improved over time, there is a lack of consensus on the ideal managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[ 1 , 3 ]. The thoracic spine is the predilected region, a characteristic shared with our case [ 4 , 9 ]. In contrast, our patient’s primary symptoms and the index operation occurred during childhood, a rarity in this context [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 61%
“…[ 1 , 3 ]. The thoracic spine is the predilected region, a characteristic shared with our case [ 4 , 9 ]. In contrast, our patient’s primary symptoms and the index operation occurred during childhood, a rarity in this context [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 61%
“… No Vasudeva et al [ 59 ] 2016 05 8–43 months 4 preoperative embolizations; 1 en bloc spondylectomy; 2 piecemeal gross-total resections; 2 subtotal resections; 3 intraoperative VPs; and 1 adjuvant radiotherapy CSF leak, wound infection DVT, and hardware failure in 1 case Gajaseni et al [ 55 ] 2017 01 12 months PE and total T10 resection No Ben Wang et al [ 45 ] 2018 20 20 months Role of Radiotherapy and surgery Not mentioned Prabhuraj et al [ 64 ] 2019 05 12 months Surgery + perioperative glue embolization. No Ji et al [ 56 ] 2019 07 Mean 51.4 months Total en bloc spondylectomy No Wei hong Xu et al [ 67 ] 2020 13 Average 62 = 19 months Decompression + Vertebroplasty + Gelatin sponge + Cement (n = 6) Decompression + Intraoperative vertebroplasty (n = 7) No Yu et al [ 57 ] 2020 06 25.8 months Single-fraction SBRT Dose was 18 Gy (range, 13–20) No Makoto Handa et al [ 60 ] 2020 15 128.4 = 88.6 months Total en bloc spondylectomy (n = 10) Piecemeal total tumor excision(n = 1) Revision procedure 2 weeks after ineffective laminectomy (n = 4) No Xu D et al [ 65 ] 2021 51 Average 5.3 = 2.1 years 16 Embolization + Decompression 19 Decompression + vertebroplasty 16 Embolisation + Decompression + Vertebroplasty No Guna et al [ ...…”
Section: Resultsmentioning
confidence: 99%
“…S ince Galibert et al 1 first reported in 1984 among patients with an aggressive vertebral angioma, percutaneous vertebroplasty (PVP) has become the standard treatment for painful thoracolumbar osteoporotic vertebral compression fractures (OVCFs), OVCF osteonecrosis, vertebral pathologic fracture, and aggressive vertebral hemangioma, despite remaining a controversial procedure. [2][3][4][5][6] However, a substantial proportion of patients undergo PVP without an adequate intraoperative analgesic procedure, and procedural pain during PVP often tends to be overlooked in clinical practice. In addition, these procedures may result in painful experiences for patients.…”
mentioning
confidence: 99%